2004
DOI: 10.1002/hon.726
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of continuous infusion versus bolus mitoxantrone in combination with cytarabine in newly diagnosed patients with acute myeloblastic leukemia

Abstract: SUMMARYMitoxantrone (MTZ) has been shown to be effective in the treatment of newly diagnosed acute myeloblastic leukemia (AML). The objective of this randomized study was to evaluate the impact of mode of administration of MTZ on the response and recurrence rates in newly diagnosed patients with AML and to compare the toxicity patterns associated with bolus and continuous infusion (CI) of MTZ. From March 1987 to March 1994, 40 newly diagnosed patients with AML were randomized to receive either bolus or CI-MTZ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…One of the reasons for the higher incidence of cardiotoxicity could be a higher induction bolus dose of mitoxantrone (80 mg/m 2 ) in the current study as compared to the 50 mg/m that has been typically utilized in the modified AIDA protocol and for induction regimens . The higher incidence of cardiotoxicity could also be due to the older population in the current study (66 ± 14 years) as compared to a median age of 30 years in a study by Koc et al, which showed that the risk of symptomatic cardiotoxicity was 5–10% in patients with AML who were treated with mitoxantrone. Also, the current study included patients with previous comorbidities including coronary artery disease, hypertension, diabetes, and atrial fibrillation that could possibly explain an increased baseline risk to develop cardiotoxicity.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…One of the reasons for the higher incidence of cardiotoxicity could be a higher induction bolus dose of mitoxantrone (80 mg/m 2 ) in the current study as compared to the 50 mg/m that has been typically utilized in the modified AIDA protocol and for induction regimens . The higher incidence of cardiotoxicity could also be due to the older population in the current study (66 ± 14 years) as compared to a median age of 30 years in a study by Koc et al, which showed that the risk of symptomatic cardiotoxicity was 5–10% in patients with AML who were treated with mitoxantrone. Also, the current study included patients with previous comorbidities including coronary artery disease, hypertension, diabetes, and atrial fibrillation that could possibly explain an increased baseline risk to develop cardiotoxicity.…”
Section: Discussionmentioning
confidence: 66%
“…Most of the current evidence on chemotherapy‐related cardiotoxicity is based on studies from breast cancer and pediatric cancer survivors who received anthracyclines and (or) trastuzumab as chemotherapeutic agents. Mitoxantrone hydrochloride is an anthracenedione that is believed to be associated with less cardiotoxicity . Most of the evidence on mitoxantrone‐related cardiotoxicity stems from studies evaluating long‐term cardiotoxic effects of low‐dose maintenance mitoxantrone therapy in patients with multiple sclerosis and from pediatric leukemia survivors .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations